Pengaruh Persepsi Atas Penggunaan Media Interaktif Canva dan Minat Belajar terhadap Hasil Belajar Matematika di SMPN 2 Cianjur - Dede Nurhayati; Supardi Supardi (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
Canva learning media is an online learning platform for graphic design in various creative designs to facilitate its users such as designing posters, infographics and presentations. Not only for designing but can be used as a learning medium for teachers, students and schools in classroom learning. The purpose of this study was to determine the influence of perceptions on the use of Canva interactive media and students' learning interests on students' Mathematics learning outcomes at SMPN 2 Cianjur. This study uses a Quantitative Approach with the Survey method. The research design used is multiple linear regression analysis. The research sample was 35 students at SMPN 2 Cianjur. Based on the results of the research data analysis, 76% of responses were obtained based on the questionnaire distributed, respondents agreed that there was an influence of perceptions on the use of Canva interactive media and students' learning interests on mathematics learning outcomes.